Recursos e capacidades que podem influenciar a inserção internacional das empresas locais de tecnologia da informação - Linn, Paula Alexandra (Universidade do Vale do Rio dos Sinos, 2012)
The increasing internationalization of companies in recent years has created opportunities for Brazilian companies to insert themselves in the international market. Within the global market, companies that provide IT services have developed. At the same time, local IT companies have developed commercial and personal relationships with multinationals installed in Brazil. This brings the chance to investigate which resources the Brazilian IT companies are acquiring by providing services to multinationals. IT companies based in the state of Rio Grande do Sul were analyzed for this study. The method of study was proposed based on a theoretical foundation that guided the current research of two companies without international operations and one with international operations, as well as a multinational that contracts local IT companies. The study concludes that the insertion of these companies occurs, for the most part due to personal relationships. However, it is reasonable to assume that the companies' certifications, professionals, experience, the actively managing founder, qualified professionals with a domain of another language, investments in innovation, research and development, as well as investments in technological infrastructure, can contribute a great deal to enhance the insertion of these companies in this ample internationalization process.
Keywords: Tecnologia da informação; Recursos; Internacionalização; Redes de relacionamento; Information technology; Resources; Internationalization; Social networks; ACCNPQ::Ciências Sociais Aplicadas::Administração